PENINGKATAN KEMAMPUAN BERPIKIR INTUITIF SISWA SMP DALAM MENYELESAIKAN SOAL UN MELALUI MODEL PEMBELAJARAN STAD BERBASIS METODE DRILL - Magfirah, Nurul; Ibrahim, Lukman; Safrina, Khusnul (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
The achievement of learning objectives through the national exam indicates that mathematics is ranked low, mathematics learning is expected to develop intuitive thinking skills. Intuitive thinking has an important to solve math problems based on knowledge and experience. The purpose of this research was to describe the process of improving students' intuitive thinking skills. This research is a classroom action research with 2 cycles. Each cycle consists of planning, acting, observing and reflecting. The research subjects were 26 students of class IX-1 SMP Negeri 10 Takengon. The results showed that STAD learning model based on the Drill method there was an increase in the ability to think intuitively. It can be seen from the test cycle I and cycle II, this increase is based on three indicators, the catalization indicator increased from 50% to 88.46%, the deduction indicator increased from 69.23% to 84.62% and the generalization indicator increased from 53.85% to 63.39%. The results of the N Gain test on the pre-test and post-test scores showed that students' abilities were in the high category.